Padi Hirida Perbandingan Kinerja Padi Sawah Inbrida dan Hibrida Beras Putih dengan Penambahan Unsur Mikro Boron pada Media Tanam - Muhammad Ikhwan Alrasyid (Balitbangda Provinsi Lampung, 2020)
Rice production needs to be increased continuously. The increase can be done by assembling superior varieties and the addition of boron. The purpose of this study was to analyze the response of boron administration, analyze hybrid and inbred differences, as well as genetic diversity and broad-sense heritability in the rice population under study. The study was conducted at the Integrated Field Laboratory and Laboratory of Seed and Plant Breeding University of Lampung, February - June 2017. The hybrids used were crossing of CSG1 and Ciherang, Gendut and CSG3, Gendut and CSG2, and Ciherang and CSG2. while the inbreds used are female elders from each of these hybrids. The study was compiled based on a factorial completely randomized group design, data tested by Barlett and Levene for homogeneity of variance. The ranking is being done using the Tukey Honestly Significant Difference (HSD). The magnitude of genetic variance and broad-sense heritability were assumed based on the expected Mean Squared on the results of the analysis of variance. The results showed that rice that was applied with 3 ppm of boron did not show any significant difference, hybrid rice had higher yields than inbred rice, there were genetic variations and broad-sense heritability seen in plant height: σ2g = 203.6 *; h2BS = 96.29 *; KKg = 13.34%, and weight of filled grain per clump: σ2g = 353.38 *; h2BS = 98.58 *; KKg = 53.06%.